Maternal soluble PD‐1 levels are significantly increased in women with preeclampsia. (17th October 2019) - Gu, Yang; Morgan, John; Lewis, David F.; Cooper, Danielle B.; McCathran, Charles E.; Wang, Yuping
Abstract: Problem: Programmed cell death‐1 (PD‐1) and its ligand (PD‐L1) have emerged as key players in regulating immune tolerance. Preeclampsia is associated with maladaptation of immune tolerance during pregnancy. This study aimed to determine if maternal soluble PD‐1 (sPD‐1) and soluble PD‐L1 (sPD‐L1) levels are altered in preeclampsia. Method of study: Maternal sPD‐1 and sPD‐L1 levels were measured by ELISA in 172 pregnant women (86 normotensive and 86 preeclampsia). The differences in sPD‐1 and sPD‐L1 levels between normotensive and preeclamptic pregnant women, <34 vs >34 weeks, and fetal gender differences were assessed. Data were analyzed by unpaired t test or chi‐square. A probability level of <.05 was considered statistically significant. Results: Maternal sPD‐1 levels were significantly higher in preeclamptic than in normotensive pregnant women, 6262 ± 1860 vs 1134 ± 349 pg/mL, P  < .01. sPD‐1 levels were not statistically different between <34 and >34 weeks of gestation in both normotensive and preeclamptic groups. sPD‐1 levels were relatively higher in mothers with female fetus than with male fetus in the preeclamptic group: 8104 ± 3054 vs 3802 ± 2177 pg/mL, but relatively lower in mothers with female fetus than with male fetus in the normotensive group: 425 ± 134 vs 625 ± 182 pg/mL. Maternal sPD‐L1 levels were relatively higher in preeclamptic than in normotensive pregnant women: 143 ± 52 vs 69 ± 13 pg/mL. Conclusion: Aberrant sPD‐1/sPD‐L1 signaling is present in preeclampsia. Whether increased maternal sPD‐1 and sPD‐L1 levels were associated with fetal gender difference or immune tolerance dissimilarity during pregnancy in women with preeclampsia warrants further investigation.